Crystallization and Mechanical Properties of Polypropylene under Processing-Relevant Cooling Conditions with respect to Isothermal Holding Time. (15th September 2016) - Fischer, Christopher; Drummer, Dietmar
Abstract : For semicrystalline thermoplastics, aside from pressure and shear, the temperature-time behavior while cooling the melt significantly affects the geometry and degree of ordered structures (e.g., spherulite size, degree of crystallization, and crystal modification) and, as a consequence, the resulting global component properties. Previous research has shown that a higher isothermal holding temperature (e.g., mold temperature and chill-roll temperature) leads to the formation of more distinct ordered structures and, therefore, can lead to greater stiffness and strength. Nevertheless, isothermal holding time during manufacturing is typically not taken into account. In this paper, fast scanning calorimetry (FSC) measurements were taken using polypropylene to analyze the crystallization during idealized temperature-time profiles based on the dynamic temperature process and to investigate the crystallization behavior at different temperatures and isothermal holding times analytically. Furthermore, iPP foils were extruded and tested mechanically to investigate the knowledge gained experimentally. Analytical and mechanical results show that foils produced at the same isothermal holding temperature can obtain significantly different ordered structures and mechanical properties depending primarily on the isothermal holding time.